PENGARUH CO – BRANDING CHATIME – SASA TERHADAP BRAND EQUITY CHATIME - Alfi Karunia Nilasari; Berlian Primadani Satria Putri (Universitas Nusa Cendana, 2023)
This study aims to find out the influence of the Chatime-Sasa Co-branding on Chatime's Brand Equity. The method in this study is a quantitative method of the causal type. The authors use a non-probability sampling type that is purposive sampling. The current target sample of the study is 100 respondents. Based on the results of the study, the Co-branding variable has a significant positive influence on Brand Equity. Chatime-Sasa's Co-branding influences Chatime's Brand Equity by 45,4% and another 54,6% is influenced by other variables outside of Co-branding. The benefit of the current research is to provide ideas and input on Chatime-Sasa Co-branding activities toward Chatime Brand Equity which can then be used as a branding strategy in the future. Keywords : Co-branding; Brand Equity; Chatime-Sasa